Formulasi Strategi Pemasaran Sepatu Piezoelektrik dengan Menggunakan Pendekatan Riset Kualitatif dan Kuantitatif - Fathkia Mutiara Khalila; Hasrini Sari (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2018)
Nowadays, battery as power source plays such a vital role but its capacity is not enough to match various features that demand quite a lot of energy and time. This research is intended to investigate the commercialization aspect of piezoelectric material for harvesting energy. This material can produce electrical charge given a mechanical tension. The combination of piezoelectric and shoe as step-on media can produce energy. The potential market for the product is investigated using qualitative research. Diffusion of Innovation Model is used as segmentation base. Next, target market is selected by evaluating each segment based on market and technology criteria using quantitave study. The result of this research showed 3 customer segments but only 1 segment is selected as target market by using concentrated marketing strategy. Based on the special characteristics and behaviors owned by the target market, a marketing program is developed to serve them.